Penggunaan Media Pembelajaran Berbasis Virtual Reality dalam Pembelajaran Sejarah di SMA 23 Makassar - Ridha, Muh. Rasyid; Amirullah, Amirullah; Malihu, La; sanur, Ilham samudra; Rifal, Rifal (Humanis, 2024)
This study aims to analyze the impact of using Virtual Reality (VR) based learning media in learning history at SMA 23 Makassar. VR technology offers an immersive learning experience with three-dimensional visualization, allowing students to explore historical events and locations virtually without leaving the classroom. The research began with planning in the form of team formation and debriefing, followed by the preparation stage for one week. Preparatory activities include communication with history educators of SMA 23 Makassar, preparation of schedules, determination of implementation locations, making broadcast materials, and procurement of supporting equipment and materials. The results showed that the use of VR had a positive impact in improving students' understanding of complex and abstract historical concepts. Students showed higher interest in learning history due to a more interesting and interactive learning atmosphere. In addition, the use of VR also contributes to the improvement of students' digital literacy, which is relevant to the 21st century skill needs. This study concludes that VR-based learning media has great potential to improve the quality of history learning if supported by the development of adequate infrastructure and content. Recommendations are given for collaboration between educators, technology developers and the government to overcome existing obstacles and maximize the benefits of this technology in education. Abstract. Penelitian ini bertujuan menganalisis dampak penggunaan media pembelajaran berbasis Virtual Reality (VR) dalam pembelajaran sejarah di SMA 23 Makassar. Teknologi VR menawarkan pengalaman belajar yang imersif dengan visualisasi tiga dimensi, memungkinkan siswa menjelajahi peristiwa dan lokasi bersejarah secara virtual tanpa meninggalkan ruang kelas. Penelitian dimulai dengan perencanaan berupa pembentukan dan pembekalan tim, dilanjutkan tahap persiapan selama satu minggu. Kegiatan persiapan meliputi komunikasi dengan pendidik sejarah SMA 23 Makassar, penyusunan jadwal, penetapan lokasi implementasi, pembuatan bahan tayang, serta pengadaan peralatan dan bahan pendukung. Hasil penelitian menunjukkan bahwa penggunaan VR memberikan dampak positif dalam meningkatkan pemahaman siswa terhadap konsep-konsep sejarah yang kompleks dan abstrak. Siswa menunjukkan minat yang lebih tinggi terhadap pembelajaran sejarah karena suasana belajar yang lebih menarik dan interaktif. Selain itu, penggunaan VR juga berkontribusi pada peningkatan literasi digital siswa, yang relevan dengan kebutuhan keterampilan abad ke-21. Penelitian ini menyimpulkan bahwa media pembelajaran berbasis VR memiliki potensi besar untuk meningkatkan kualitas pembelajaran sejarah jika didukung dengan pengembangan infrastruktur dan konten yang memadai. Rekomendasi diberikan untuk kolaborasi antara pendidik, pengembang teknologi, dan pemerintah guna mengatasi kendala yang ada dan memaksimalkan manfaat teknologi ini dalam pendidikan.